Yarbus's Conceptions on the General Mechanisms of Color Perception. (August 2015) - Nikolaev, Petr P.; Rozhkova, Galina I.
In the last series of papers published during 1975 to 1980, Alfred Yarbus tried to formulate general conceptions concerning the basic principles of retinal image processing in the human visual system. The original ideas of Yarbus were based on the results of his numerous and various experiments carried out with extraordinary inventiveness and great skill. Being concentrated primarily on the problems of color vision, Alfred Yarbus dreamed of elaborating a comprehensive model that would simulate visual information processing at the monocular precognitive level in the visual system of humans with normal trichromatic color perception. In this article, the most important of Yarbus' experimental paradigms, findings, statements, and conclusions are systematized and considered in relation to the classical theories of color perception and, in particular, fundamental theses of the Nyberg school. The perceptual model developed by Alfred Yarbus remained incomplete. Nevertheless, it is already evident that some intrinsic contradictions make it inadequate in terms of comprehensive modeling. However, certain partial advantages deserve more thorough appreciation and further investigation.